Clinical outcomes of rib graft use in rhinoplasty: a meta-analysis - Qian Wang; Jing Liu; Zhixing Chen (BMC Surgery)
Abstract Background Rib cartilage rhinoplasty has emerged as a preferred surgical approach for complex nasal reconstructions due to its structural integrity, versatility, and long-term stability. This systematic review and meta-analysis evaluates the complication rates and patient satisfaction outcomes associated with rib cartilage rhinoplasty to provide a comprehensive assessment of its safety and efficacy. Methods A systematic search was conducted across PubMed, Google Scholar, and the Cochrane Library to identify relevant studies. Inclusion criteria were original studies reporting complication rates or patient satisfaction following rib cartilage rhinoplasty with a minimum follow-up of six months. Data synthesis was performed using a random-effects model, and heterogeneity was assessed using the I² statistic. Forest plots and funnel plots were generated to summarize findings and evaluate publication bias. Results A total of six studies were included, comprising 888 patients. The pooled complication rate was 7% (95% CI: 5–9%) under the fixed-effects model and 8% (95% CI: 3–20%) under the random-effects model, with substantial heterogeneity (I² = 79.3%, p = 0.0002). Complications were predominantly minor, including infection, warping, and graft displacement. Patient satisfaction rates were consistently high, with a pooled proportion of 92% (95% CI: 90–94%) under the fixed-effects model and 89% (95% CI: 60–98%) under the random-effects model. Significant heterogeneity was observed (I² = 86%, p < 0.0001). Funnel plots indicated potential publication bias, particularly in studies reporting patient satisfaction. Conclusions Rib cartilage rhinoplasty demonstrates a favorable safety profile and high patient satisfaction, making it a reliable option for complex nasal reconstructions. The low complication rates, combined with excellent aesthetic and functional outcomes, underscore the efficacy of this technique.